Study on the Problems and Countermeasures of Specially Invited Mediation’s System in China Under the Diversified Dispute Resolution Mechanisms - Yuna Wu (Studies in Law and Justice, 2024)
The Provisions of the Supreme People’s Court on Specially Invited Mediation in the People’s courts, issued in 2016, formally established the specially invited mediation’s system, but the lack of uniform standards for the rules applicable to the specially invited mediation’s system, the unsoundness of safeguard mechanism, and the inefficiency of its operation have not been effectively resolved. Therefore, the scope of application of the specially invited mediation’s system should be clarified through legislation, the entry threshold of specially invited mediators should be raised, a perfect financial guarantee system for specially invited mediation should be established, and a reward and punishment mechanism should be set up to strengthen the punishment for false mediation, preventing false mediation, and increasing the supervision of the specially invited mediation procedure, so as to promote the orderly conduct of specially invited mediation and efficiently resolve disputes.